Does diversity matter? exploring workforce diversity, diversity management, and organizational performance in social enterprises. Issue 3 (29th June 2017) - Cho, Sangmi; Kim, Ahraemi; Mor Barak, Michàlle E.
Abstract : This study explores the dynamics of workforce diversity, diversity management, and organizational performance in social enterprises. Semi‐structured in‐depth interviews were conducted with 14 individuals working in the social enterprise sector in Los Angeles, California, including both top management and regular employees. Data were analyzed using thematic analysis rooted in grounded theory. Overall, high levels of diversity in gender, race/ethnicity, education, and sexual orientation were identified in social enterprises, while low levels of age and value diversity were found. Workforce diversity and diversity management were reported to be crucial factors that positively influence organizational performance. Although interviewees considered diversity management to play an important role in promoting organizational performance, they were less likely to implement diversity management themselves. By providing important insights into workforce diversity, diversity management, and organizational performance in social enterprises, this study contributes to an understanding of the dynamics and provides suggestions for sustainability in social enterprises.